Communication Problem Between International Students and American Students - Yang, Zirui; Zhou, Luoluo; Choong, Catrena; Chen, Jiameng; Yang, Yuchen; Christensen, Ami (My University, 2019)
Our research goal is to reduce the communication and language barrier between international students and American students for a better learning environment. We used our survey to collect the data for our research. Many international students who are nonnative speakers of English experience culture shock when studying in a different country. Therefore, this research is important to understand how to overcome communication barriers among international and local students.
Color poster with text, charts, and graphs.
Keywords: International students; College students; Intercultural communication; Posters